IMPLEMENTASI PROGRAM JAMINAN KESEHATAN NASIONALTERHADAP PELAKSANAAN PELAYANAN PROMOTIF DAN PREVENTIF DI PUSKESMAS KECAMATAN KRAMAT JATI KOTAJAKARTA TIMUR TAHUN 2019 - Nadia (2020)
JKN (Jaminan Kesehatan Nasional) is a form of health insurance that was held using the mechanism of social insurance and it is deemed mandatory to all Indonesian citizen, its purpose is also to fill the people's basic health needs. For that to be achieved, BPJS Kesehatan pushes FKTP, especially Puskesmas or public health centers, to raise program innovations especially promotive and preventive services. The goal of this study is to analize JKN's programs implementation that was held by BPJS Kesehatan on the promotive and preventive services in Puskesmas Kramat Jati Jakarta Timur. This is a descriptive study using qualitative design with 10 research informants and this research used interviews to collect data. The result of this study shows that the implementation of the promotive and preventive services in Puskesmas Kramat Jati before and after the JKN's programs were held didn't have any significant changes. The change that do happened, is the funding and the policy related to JKN. There were some obstacles, for example, the time organization and to raise SPM (Standar Pelayanan Minimal), the lack of coordination between health workers, and the lack of pariticipation from the people on the programs that the Puskesmas held, in the effort to provide health services the things that are certainly needed are the quantity, quality, and diversity of health workers that are distributed evenly depending on what is needed in providing healthcare. It can be concluded from this research that the indicator for a successful promotive and preventive services cannot be seen from only one factor, also the implementation of JKN's program doesn't necessarily effect the promotive and preventive services because the funding still uses the fund from BOK (Bantuan Operasional Kesehatan), whilst capitation funding that got into BLUD (Badan Layanan Umum Daerah) was used more to fun health workers and UKP services